The normal electrocardiograms in the conscious newborn lambs in neonatal period and its progression. Issue 1 (December 2015) - Koether, Karoline; Ulian, Carla; Lourenço, Maria; Gonçalves, Renato; Sudano, Mateus; Cruz, Raíssa; Branchini, Naiana; Alfonso, Angélica; Chiacchio, Simone
Abstract Background Veterinary cardiology, especially electrocardiography, has shown major advancements for all animal species. Consequently, the number of ovine species used as experimental animals has increased to date. Few studies have been published on ovine systematic electrocardiography, particularly with respect to lamb physiology and neonatology. This study aimed to standardize the values of normal waves, complexes, and intervals of the electrocardiogram (ECG) in clinically Bergamasca healthy neonatal lambs, used as experimental animals. Serial computerized electrocardiography was performed in 10 male and 12 female neonates on the 1st, 7th, 14th, 21st, 28th, and 35th days of age. The following parameters were analyzed: heart rate and rhythm, duration and amplitude of waves, duration of intervals, and heart electrical axis. Results During the first 35 days of life, (1) the sinusal heart rhythm was predominant, (2) there was a progressive decrease in the heart rate and R and T wave amplitude, and (3) a progressive increase in the PR, QT, and RR intervals. Finally, we confirmed that various components of neonatal evolution were more discernible in the augmented unipolar leads (aVF), which we recommend should be preferentially used in future studies. No significant statistical alterations were observed between males and females in relation to the analyzed parameters. Conclusions The information assimilated in this study is anticipated to enhance the diagnosis of multiple congenital heart defects in Bergamasca lambs and could be implemented in studies that use ovine species as experimental models.